Evaluation of Antibacterial Assays for Screening of Marine Invertebrate Extracts - Nurrahmi Dewi Fajarningsih; Ifah Munifah; Dewi Seswita Zilda (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Marine environment continuously produces pharmacologically active compounds. To screen marine natural products as a source of potential antibiotics, it is very important to select an accurate and efficient antibacterial assay. This study aims to find out the best assay for screening of antibacterial activity of marine invertebrate extracts by comparing the performance of 3 methods, i.e. the colorimetric resazurin microtiter assay (REMA), disc diffusion assay and spectrophotometric microdilution assay (SMA). Five marine invertebrate extracts, i.e. Stylissa sp., Theonella sp., Lobophytum sp., Sarcophyton sp., and Aaptos sp., were tested using those 3 different methods. The best method obtained was then further tested for its performance to screen 126 marine invertebrate extracts against 2 bacterial strains i.e. Escherichia coli (ATCC®25922TM) and Staphylococcus aureus (ATCC®25923TM). The study showed that, resazurin microtiter assay (REMA) was simpler, produced quicker result and able to generate reliable data for antimicrobial activity screening compared to the other methods. Moreover, REMA assay is regarded as a suitable assay platform to be implemented for screening of marine invertebrate extracts antibacterial activity since it requires only a small amount of extracts. Based on the MIC values, amongst 126 marine invertebrate extracts screened, 59; 36; 25 and 6 extracts tested against E. coli and 69; 36; 18; and 3 extracts tested against S. aureus were respectively categorized as not active, moderately potential, potential and very potential sample worth to be analyzed further. The ability of the REMA to generate accurate MIC value, which is comparable to the existing antibiotic drug MIC value, will empower researchers to decide whether the extracts worth to be examined further or not.